2004
DOI: 10.1097/01.tp.0000120949.86038.62
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain After Renal Transplantation Is a Risk Factor for Patient and Graft Outcome

Abstract: BMI has a strong association with outcomes after renal transplantation independent of most of the known risk factors for patient and graft survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(93 citation statements)
references
References 20 publications
5
81
0
7
Order By: Relevance
“…Recent data from a contemporary cohort of the United Network for Organ Sharing database indicated that 50% of transplant patients could be classified as obese or morbidly obese (20). Obesity can predispose to insulin resistance, diabetes, ischemic heart disease, and reduced graft survival (9, 21,22). Obesity in transplant patients is also being increasingly recognized in the context of the metabolic syndrome, which is defined in Table 2.…”
Section: Obesitymentioning
confidence: 99%
“…Recent data from a contemporary cohort of the United Network for Organ Sharing database indicated that 50% of transplant patients could be classified as obese or morbidly obese (20). Obesity can predispose to insulin resistance, diabetes, ischemic heart disease, and reduced graft survival (9, 21,22). Obesity in transplant patients is also being increasingly recognized in the context of the metabolic syndrome, which is defined in Table 2.…”
Section: Obesitymentioning
confidence: 99%
“…13 According to De Oliveira and associates, weight gain after transplant is common and is seen in both patients who were obese and patients who were not obese before transplant. 14 Others have also documented that weight gain often emerges in the first year after transplant 11,15,16 and is a common problem for patients, especially during the first 6 months. Weight gain after transplant has been shown to be from 6 to 10 kg, with average body mass index increasing between 2 and 3.8 kg/m 2 .…”
Section: Resultsmentioning
confidence: 99%
“…More weight gain has been documented in patients who are moderately obese at the time of transplant than in non-obese patients. 3,56 El-Agroudy and research team 23 documented that weight gain occurred in the first 6 months following transplant and that weight gain tended to increase after that but at a slower rate. They speculated that this weight gain could be attributed to nutritional intake, lessened rates of activity and a higher amount of steroids in their pharmacological protocol.…”
Section: Health Outcomes Of Weight Gain In Healthy Adultsmentioning
confidence: 99%
“…Immunosuppressant medications can also affect body fat distribution and the retention of excess fluid may cause weight gain in the post transplant recipient. 2,23 Significant hyperglycemia and post transplant diabetes are also common side effects of not only corticosteroids, but also seen with other immunosuppressive agents such as cyclosporine and tacrolimus. 24 In addition, cyclosporine, tacrolimus and sirolimus, along with corticosteroids may contribute to the metabolic changes following kidney transplantation as the body is attempting to adjust from its previous state of uremia.…”
Section: List Of Tablesmentioning
confidence: 99%
See 1 more Smart Citation